Biochemical and functional properties of a thrombin-like enzyme isolated from Bothrops pauloensis snake venom - Costa, Fabio L. S.; Rodrigues, Renata S.; Izidoro, Luiz F. M.; Menaldo, Danilo L.; Hamaguchi, Amelia; Homsi-Brandeburgo, Maria I.; Fuly, Andre L.; Soares, Sandro G.; Selistre-de-Araujo, Heloisa S.; Barraviera, Benedito [UNESP]; Soares, Andreimar M.; Rodrigues, Veridiana M. (Pergamon-Elsevier B.V. Ltd, 2009)
In the present study, a thrombin-like enzyme named BpSP-I was isolated from Bothrops pauloensis snake venom and its biochemical, enzymatic and pharmacological characteristics were determined. BpSP-I is a glycoprotein that contains both N-linked carbohydrates and sialic acid in its structure, with M(r) = 34,000 under reducing conditions and pI similar to 6.4. The N-terminal sequence of the enzyme (VIGGDECDINEHPFL) showed high similarity with other thrombin-like enzymes from snake venoms. BpSP-I showed high clotting activity upon bovine and human plasma and was inhibited by PMSF, benzamidine and leupeptin. Moreover, this enzyme showed stability when examined at different temperatures (-70 to 37 degrees C), pH values (3-9) or in the presence of divalent metal ions (Ca(2+), Mg(2+), Zn(2+) and Mn(2+)). BpSP-I showed high catalytic activity upon substrates, such as fibrinogen, TAME, S-2238 and S-2288. It also showed kallikrein-like activity, but was unable to act upon factor Xa and plasmin substrates. Indeed, the enzyme did not induce hemorrhage, myotoxicity or edema. Taken together, our data showed that BpSP-I is in fact a thrombin-like enzyme isoform isolated from Bothrops pauloensis snake venom. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bothrops (neuwiedi) pauloensis; Blood coagulation; Proteolytic enzymes; Serine proteinase; Thrombin-like enzymes